Risperidone-Induced Renal Damage and Metabolic Side Effects: The Protective Effect of Resveratrol - Bilgic, Sedat; Korkmaz, Deniz Tastemir; Azirak, Sebile; Guvenc, Ayse Nilay; Kocaman, Nevin; Ozer, Mehmet Kaya (Hindawi Ltd, 2017)
Objective. The aim of the study was to investigate the possible protective qualities of resveratrol (RSV) against the side effects of risperidone (RIS) in an experimental model in rat kidneys with histologic and biochemical assessments. Materials and Methods. Experimental procedures were performed on 35 female Sprague Dawley rats. Rats were randomly divided into five groups: control, untreated rats (n = 7) were in group 1; group 2 was given 2 mg/kg/day RIS (n = 7); group 3 was treated with 2 mg/kg/day RIS and 20 mg/kg/day RSV (n = 7); group 4 was treated with 2 mg/kg/day RIS and 40 mg/kg/day RSV (n = 7); and group 5 was treated with 2 mg/kg/day RIS and 80 mg/kg/day RSV (n = 7). All treatments were administered for two weeks by gavage. On treatment day 15, kidney tissues were removed for analysis. Results. The results showed that RSV treatment reduced weight gain induced by RIS. In addition, RSV increased the total antioxidant status (TAS) and decreased serum creatinine (Cr), blood urea nitrogen (BUN), oxidative stress index (OSI), and total oxidant status (TOS) levels significantly (p < 0 05). Conclusion. This study revealed that treatment with RSV might protect kidney tissues against the side effects of RIS. RSV could be an effective course of therapy to enhance therapeutic efficacy.
Keywords: Acute Kidney Injury; Atypical Antipsychotic-Drugs; Oxidative Stress; in-Vitro; Rats; Excretion; Cytokines; Survival; Health; Model